VIDEO EDUKASI CUCI TANGAN SEHAT SEBAGAI PROGRAM PENGENDALIAN DAN PENCEGAHAN COVID-19 - Mahyarudin; Andriani; Rini Andriani; Willy Handoko (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a new strain of virus from the coronavirus that can cause mild, severe respiratory disorders, and even death. The disease is called Coronavirus Disease (20) 19 or COVID-19. The virus is transmitted via droplets spread by coughing or sneezing on an infected person. A clean and healthy lifestyle, and trying to protect ourselves by doing healthy hand washing is one of the ways to prevent the spread of this more massive virus. The community is at the forefront of preventing the spread of COVID-19. The role of public knowledge is very important to prevent the spread of COVID 19 to the family level. This activity aims to provide education to the public on the importance of healthy hand washing to prevent the spread of COVID-19. The target of this activity is the people in Pontianak City. The output of this activity is that the community understands the importance of clean and healthy behavior for disease prevention so that they are more disciplined in carrying out healthy hand washing.